Faktor-Faktor yang memengaruhi Tingkat Kepatuhan Wajib Pajak Orang Pribadi di KPP Wilayah DKI Jakarta - Joseline Natasha; Aan Marlinah (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to analyze the factors that influence individual taxpayer compliance. The factors referred to in this study are the taxpayers understanding, awareness of taxpayer, taxes sanction, environment of taxpayer, quality of service, moral obligations, perceived behavioral control, and e-filing. The form of research that will be used in this study is causality. The data collection technique used in this research is a questionnaire. The object of this research is an individual taxpayer at the DKI Jakarta Regional Tax Office. The sampling method used is convenience sampling with 65 samples. The results of this study conclude that the taxpayers understanding affects the compliance of individual taxpayers at the DKI Jakarta Regional Tax Office. This means that the higher taxpayer understands of the tax laws and regulations in Indonesia, the higher the compliance of individual taxpayers. Meanwhile, awareness of taxpayer, taxes sanction, environment of taxpayer, quality of service, moral obligation, perceived behavioral control, and e-filing has no effect on individual taxpayer compliance in the DKI Jakarta Regional Tax Office.